Yield Stability of Sixteen Rice Genotypes in White Nile Sate, Sudan - . Mohamed, Khalid A (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of the present investigation was to analyze the pattern of Genotype x Environment (G x E) interaction for grain yield of sixteen rice genotypes using Additive Main effects And Multiplicative Interaction (AMMI) model. Genotypes were grown at two locations (Ed- duim and Kosti, White Nile State, Sudan) for two years. Main effects due to environment (E), genotypes (G) and GxE interaction (GEI) were significant (p<0.01), with highest variation (63.3%) accounted for by environmental effects. The first Interaction Principal Component Axes (IPCA 1) was significant (p<0.01) and contributed 72.4% of the total GEI. The biplot was identified genotypes and testing environments that exhibited major sources of GE interaction as well as those that were stable. YUNLU 33 was identified as the best genotype (higher yielding and stable)